The Imaginations of Unreasonable Men inspiration, vision, and purpose in the quest to end malaria by bill shore - Shore, Bill (New York Public Affairs, 2010)
A small cadre of scientists?collaborators and competitors?are determined to develop a vaccine for malaria?a feat most tropical disease experts have long considered impossible. Skepticism, doubt, and a host of logistical and financial obstacles dog their quest. Success may ultimately elude them. Why, and how, do they persist?
Includes index